Dietary vitamin K intake in relation to skeletal muscle mass and strength among adults: a cross-sectional study based on NHANES - Wang, Qiong; Chen, Pei-pei; Guo, Jia-yu; Wang, Shi-jia; Bao, Yuan-yuan; Zhang, Yu; Yu, Kang (Frontiers in Nutrition, 2024)
Background: Previous studies revealed that vitamin K might help maintain muscle homeostasis, but this association has received little attention. We aimed to explore the associations of vitamin K intake with skeletal muscle mass and strength. Methods: We included cross-sectional data from the U.S. National Health and Nutrition Examination Survey (NHANES, 2011-2018). Vitamin K intake was assessed via 24-hour recall. Covariate-adjusted multiple linear regression and restricted cubic splines were used to evaluate the associations of dietary vitamin K intake with skeletal muscle mass and strength, measured by dual-energy X-ray absorptiometry and handgrip dynamometer, respectively. Results: Dietary vitamin K intake was positively associated with skeletal muscle mass in males (β=0.05747, P=0.0204) but not in females. We also revealed a positive association between dietary vitamin K intake and handgrip strength within the range of 0-59.871 µg/d (Pnonlinear=0.049). However, beyond this threshold, increasing vitamin K intake did not cause additional handgrip strength improvements. Conclusions: We provided evidence for a positive relationship between dietary vitamin K intake and skeletal muscle mass in males. Moreover, our study revealed a nonlinear relationship between dietary vitamin K intake and handgrip strength, highlighting an optimal intake range.